PENGARUH JUMLAH PRODUKSI DAN KUALITAS SDM TERHADAP PENDAPATAN KARYAWAN PADA KONVEKSI HIJAB AL – VIETA TUNGGUL PACIRAN - Abdul Ghofur; Mohammad Rizal Nur Irawan; Andi Farouq Hasan (Media Mahardhika, 2020)
Community income becomes a reference that an area is considered prosperous. The existence of the industrial revolution 4.0 makes the spirit for the community to compete to improve the quality of community resources so that they are not colonized by technological sophistication. This study aims to analyze and discuss the effect of the amount of production and quality of human resources on employee income in the Al-Vieta hijab convection. The research method used is quantitative research. The sample used is a saturated sampling of production employees with 25 respondents. Analysis of the data used is validity, reliability, classic assumption test and multiple linear regression using SPSS 20. The mathematical model as a representation of the effect of the number of production and quality of HR on employee income in hijab convection Al-Vieta. The results showed that there was an effect simultaneously on the amount of production and the quality of human resources on employee income at the Al-Vieta hijab convection. The results of the coefficient of determination (R ^ 2) of 0.725, meaning that the amount of production and quality of human resources contribute to affect employee income by 72.5% while the remaining 27.5% is influenced by other variables outside the variables studied by researchers.